User's Expectations on Interactive Travel Guide e-Book: A Case Study - Siti Shukhaila, Shaharuddin (Universiti Malaysia Sarawak, (UNIMAS), 2016)
This research presented the possible multimedia features for travel guide eBook services based on user's expectations. It examined whether user's requirements were valid and reliable, and to propose if adjustement and new phenomena could be identified to further suggest implementation model of mobile travel guide eBook/ book app.